2004
DOI: 10.1002/ceat.200402055
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation of Cinnamaldehyde over Pt‐Modified Molecular Sieve Catalysts

Abstract: The catalytic properties of various Pt-modified molecular sieves were tested in liquid-phase hydrogenation of cinnamaldehyde and compared to Pt/MgO and commercial Pt/C catalysts. The type of support considerably influenced the catalytic properties. The superior selectivity performance of microporous catalysts was confirmed; the highest selectivity to allyl alcohol of about 40 % was obtained over the beta support whereas the mesoporous MCM-41-supported catalyst was unselective. The highest activity was obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…36 Murzin and co-workers found a decrease in the selectivity to unsaturated alcohol with increasing support acidity in cinnamaldehyde hydrogenation over Pt-modified molecular sieves catalysts. 42 Similar results were obtained over Ru/Al 2 O 3 catalysts, 43 inferring that the hydrogenation of the CC bond is promoted by the acid sites. Thus, it is rational to relate the selectivity patterns observed on the Ru−B/ZrO 2 -M, Ru−B/ZrO 2 -A, and Ru−B/ZrO 2 -T catalysts to the difference in the acidity of the ZrO 2 supports.…”
Section: Taking Into Account Of the Results Presented In Table 2 Andsupporting
confidence: 56%
See 2 more Smart Citations
“…36 Murzin and co-workers found a decrease in the selectivity to unsaturated alcohol with increasing support acidity in cinnamaldehyde hydrogenation over Pt-modified molecular sieves catalysts. 42 Similar results were obtained over Ru/Al 2 O 3 catalysts, 43 inferring that the hydrogenation of the CC bond is promoted by the acid sites. Thus, it is rational to relate the selectivity patterns observed on the Ru−B/ZrO 2 -M, Ru−B/ZrO 2 -A, and Ru−B/ZrO 2 -T catalysts to the difference in the acidity of the ZrO 2 supports.…”
Section: Taking Into Account Of the Results Presented In Table 2 Andsupporting
confidence: 56%
“…Researchers have evidenced that the product selectivity was influenced by the support acidity in many selective hydrogenation reactions. ,, Volckmar et al found that a high total amount of acid sites and a high amount of strong Lewis acid sites on the Ag/SiO 2 –Al 2 O 3 catalysts induced a low selectivity to allyl alcohol in acrolein hydrogenation . Murzin and co-workers found a decrease in the selectivity to unsaturated alcohol with increasing support acidity in cinnamaldehyde hydrogenation over Pt-modified molecular sieves catalysts . Similar results were obtained over Ru/Al 2 O 3 catalysts, inferring that the hydrogenation of the CC bond is promoted by the acid sites.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…The catalytic activity also depends on the acidity or the basicity and structural characteristics (particles size and porosity) of the support [29,30]. Different types of supported palladium catalysts such as Pd/carbon [31,32], Pd/SiO2 [33], Pd/Al2O3 [34], Pd/TiO2 [35], Pd/Fe2O3@C [36] have been reported to be efficient catalytic system for the hydrogenation of cinnamaldehyde.…”
Section: Introductionmentioning
confidence: 99%